Advancing endoscopic traction techniques in endoscopic submucosal dissection - Khan, Suliman; Ali, Faisal S.; Ullah, Saif; Huang, Xue-; Li, Hongyu (Frontiers in Oncology, 2022)
Traction techniques have emerged as a desirable “second-hand” while performing endoscopic submucosal dissection (ESD), enabling adequate visualization of submucosal tissue and vasculature, which allows for safe and efficient dissection. Multiple traction techniques have been developed over the years, and these can be broadly divided into internal and external traction techniques. This arsenal of techniques allows for traction that is personalized to the location of the lesion undergoing ESD. Mastering traction techniques requires structured training, and understanding of the benefits and pitfalls of each technique. Future research and development efforts need to focus on pathways and curriculums for trainees to master the currently available endoscopic traction techniques and provide avenues for the development of newer traction modalities.